The Influence of Transformational Leadership, Work Culture and Work Commitment on the Work Productivity of PT Sari Tuna Makmur Bitung Employees - Rifky, Muhammad; N. Taroreh, Rita; Ch Kawet, Raymond (Formosa Journal of Applied Sciences, 2024)
This research tries to determine the relationship between work culture, work dedication, and transformational leadership of PT Sari Tuna Makmur Bitung on productivity. The population of this study was 150 employees of PT Sari Tuna Makmur, using one hundred respondents as the sample size. Questionnaires were used in this research to collect data. Questionnaire respondents were asked to write down their responses to a number of questions. Research variables in the focus of this research are work culture, dedication, productivity and transformational leadership. The first part of the questionnaire asks questions about the respondent's personal information. The second part asks questions about the research variables.